Kick starting MLS implementation for climate change adaptation in Kenya, Tanzania and Uganda led to access to 400 accessions of MLS materials by 1000 farmers - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
400 accessions of beans, sorghum and finger millet from the Multilateral System i.e National gene banks of Kenya, Uganda and Tanzania were exchanged suing SMTAs. These have been multiplied and made available for farmers to evaluate using participatory methods. 1000 farmers in 4 sites have evaluated and pre-selected better performing varieties of sorghum, finger millet and beans. Evlautaion is still on-going in Kenya